Outer Space: is it a global common? - Kaul, Ranjana (Frontiers in Space Technologies, 2024)
This article examines critical questions related to whether Outer Space is a Global Common, including the challenge of achieving balance between the OST mandate of compliance with the common interest principle and the requirement of providing an environment for commercial lunar enterprises to succeed, and to simultaneously ensuring possibility of conflict on the Moon.